2020
DOI: 10.1021/acs.inorgchem.0c00690
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Pyclen-Based Gd3+ Complex with High Relaxivity and pH Response

Abstract: We report the synthesis and characterization of the macrocyclic ligand 2,2′-((2-(3,9-bis­(carboxymethyl)-3,6,9-triaza-1­(2,6)-pyridinacyclodecaphane-6-yl)­ethyl)­azanediyl)­diacetic acid (H4L) and several of its complexes with lanthanide ions. The structure of the free ligand was determined using X-ray diffraction measurements. Two N atoms of the pyclen moiety in the trans position are protonated in the solid state, together with the exocyclic N atom and one of the carboxylate groups of the ligand. The relaxiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…A noteworthy member of this class of macrocyclic ligands is 3,6,9-triaza-1-(2,6)-pyridinacyclodecaphane ( L1 , Figure ) which, in the three decades since its appearance, has given rise to a large family of derivatives that have been investigated for applications in many areas, including, among others, pharmaceutical and biomedical sectors, catalysis, and chemosensing as well as in the preparation of polybromides and polyiodides , featuring iodine-dense three-dimensional networks that might open up new perspectives in crystal engineering and in the design of solid-state conductors as well as in the preparation of new chemicals with antimicrobial activity. …”
Section: Introductionmentioning
confidence: 99%
“…A noteworthy member of this class of macrocyclic ligands is 3,6,9-triaza-1-(2,6)-pyridinacyclodecaphane ( L1 , Figure ) which, in the three decades since its appearance, has given rise to a large family of derivatives that have been investigated for applications in many areas, including, among others, pharmaceutical and biomedical sectors, catalysis, and chemosensing as well as in the preparation of polybromides and polyiodides , featuring iodine-dense three-dimensional networks that might open up new perspectives in crystal engineering and in the design of solid-state conductors as well as in the preparation of new chemicals with antimicrobial activity. …”
Section: Introductionmentioning
confidence: 99%
“…It was later in the spotlight for its ability to form metal complexes [6][7][8], but its wider success was achieved thanks to its utilisation as a scaffold for the preparation of new materials that have proven effective in a variety of applications. Indeed, L derivatives decorated with different hanging functionalities have been studied for several biomedical (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25]…”
Section: Introductionmentioning
confidence: 99%
“…Anion-π interactions were also found to play an important role in the formation of highly organised polyiodide complexes [44,45] and iodide based permutable organised frameworks (POF) [46] with a pyridinium-based ligand such as Stoddart's blue box (BB, cyclobis(paraquat-p-phenylene)). (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, it has been shown that L and its N-trimethylated derivative are capable of stabilising iodine-dense three-dimensional networks that might be relevant for crystal engineering purposes and the design of solid-state conductors [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26−31 Albelda et al developed a pyclen-based complex exhibiting pH-responsive behavior, as the number of coordinated water molecules varies at different pH values from 1 to 2, which results in a change of relaxivity. 32 Tircso et al reported a pH-sensitive MRI probe, PC2A-EA, which contains an ethylamine moiety that can respond within the biologically relevant pH range. 11 In 2022, a heptadentate gadolinium complex called gadopiclenol was approved as a new MRI contrast agent for imaging the central nervous system and the body of adults and children aged 2 years and above.…”
Section: ■ Introductionmentioning
confidence: 99%